1997
DOI: 10.1177/002215549704501204
|View full text |Cite
|
Sign up to set email alerts
|

Regional and Ultrastructural Immunolocalization of Copper-Zinc Superoxide Dismutase in Rat Central Nervous System

Abstract: SUMMARYWe examined the distribution of copper-zinc superoxide dismutase (CuZn-SOD) in adult rat central nervous system by light and electron microscopic immunocytochemistry, using an affinity-purified polyclonal antibody. The enzyme appeared to be exclusively localized in neurons. No immunoreactivity was seen in non-neuronal cells. The staining intensity was variable, depending on the brain region and, within the same region, on the neuron type. Highly immunoreactive elements included cortical neurons evenly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 55 publications
5
25
0
Order By: Relevance
“…MEDIC is described in more detail elsewhere (Hill et al 2004;Hill, Macosko and Holzwarth, in preparation). Using the MEDIC technique 0.1 µm diameter polystyrene beads moving 1 µm/s are at the limit of detectability, thus likely candidates for the vesicular organelles that we observe in this paper are mitochondria (Friberg et al 1998), lysosomes (Bednarski et al 1997), peroxisomes (Moreno et al 1997), and phagosomes (Martin et al 1999)-all of which are larger than 0.1 µm in neuronal cells.…”
Section: Microscopy and Image Acquisitionmentioning
confidence: 69%
“…MEDIC is described in more detail elsewhere (Hill et al 2004;Hill, Macosko and Holzwarth, in preparation). Using the MEDIC technique 0.1 µm diameter polystyrene beads moving 1 µm/s are at the limit of detectability, thus likely candidates for the vesicular organelles that we observe in this paper are mitochondria (Friberg et al 1998), lysosomes (Bednarski et al 1997), peroxisomes (Moreno et al 1997), and phagosomes (Martin et al 1999)-all of which are larger than 0.1 µm in neuronal cells.…”
Section: Microscopy and Image Acquisitionmentioning
confidence: 69%
“…Sequence analysis of CCS revealed a potential peroxisomal localization sequence in the carboxyl terminus (Fig. 1), and although recent studies have suggested that in neurons SOD1 is localized in part to peroxisomes (32), no overlap was observed for either SOD1 or CCS when double-immunofluorescent studies were performed in these same cells utilizing a sheep anti-human catalase antibody that identified peroxisomes (data not shown).…”
Section: Sod1 and Ccs Interaction 23627mentioning
confidence: 86%
“…At present it is possible to localize and quantify the amount of SOD enzyme immunohistochemically by use of specific antibodies, but not its activity (Moreno et al 1997).…”
Section: S Uperoxide Anions (Omentioning
confidence: 99%